Rotational Atherectomy in a Patient with Acute ST-Elevation Myocardial Infarction and Cardiogenic Shock - Showkathali, Refai; Sayer, Jeremy W. (International Journal of Angiology, 2013)
Rotational atherectomy (rotablation) of coronary artery is relatively contraindicated in high thrombotic state such as acute ST-elevation myocardial infarction (STEMI) because of the risk of platelet activation by the rotablator. We present a case where rotablation was necessary to recanalize the right coronary artery in a patient presenting with acute STEMI complicated by cardiogenic shock, after unsuccessful attempts with balloon catheters. He improved remarkably after the procedure and was discharged after 4 days.
Keywords: angioplasty; atherectomy; MI; stent; reperfusion; myocardial infarction; PCI